2017
DOI: 10.3390/nu9091025
|View full text |Cite
|
Sign up to set email alerts
|

Association between Dietary Carotenoid Intake and Bone Mineral Density in Korean Adults Aged 30–75 Years Using Data from the Fourth and Fifth Korean National Health and Nutrition Examination Surveys (2008–2011)

Abstract: Age-related bone loss is a major public health problem. This cross-sectional study examined the association between the dietary intake of carotenoids and bone mineral density (BMD). Data from 8022 subjects (3763 males and 4259 females) aged 30–75 years included in the Korean National Health and Nutrition Examination Survey (2008–2011) were analyzed. BMD was measured by dual-energy X-ray absorptiometry. Intake of carotenoids was estimated using 24-h dietary recall. In multiple linear analysis, after adjusting f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 43 publications
4
33
0
Order By: Relevance
“…36 In addition, the Korean national health and nutrition examination surveys among three groups, men, menopausal women, and postmenopausal women, showed that men's dietary carotenoid intake was the lowest. 57 Since fruits and vegetables are the main sources of dietary carotenoids, this study was consistent with the above findings that men consume less dietary fruits and vegetables than women. This difference in diet might explain the results in our study, with a significant decrease in prevalence and grades of atrophy/IM in the corpus only in females.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…36 In addition, the Korean national health and nutrition examination surveys among three groups, men, menopausal women, and postmenopausal women, showed that men's dietary carotenoid intake was the lowest. 57 Since fruits and vegetables are the main sources of dietary carotenoids, this study was consistent with the above findings that men consume less dietary fruits and vegetables than women. This difference in diet might explain the results in our study, with a significant decrease in prevalence and grades of atrophy/IM in the corpus only in females.…”
Section: Discussionsupporting
confidence: 91%
“…In the study of dietary intake of phytonutrients in relation to fruit and vegetable consumption in Korea, a higher proportion of women than men met the recommended intake of fruits and vegetables . In addition, the Korean national health and nutrition examination surveys among three groups, men, menopausal women, and postmenopausal women, showed that men's dietary carotenoid intake was the lowest . Since fruits and vegetables are the main sources of dietary carotenoids, this study was consistent with the above findings that men consume less dietary fruits and vegetables than women.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, Ma et al [11] reported a link between heteroplasmy levels in urine sediment and the common clinical phenotypes of m.3243A>G mutation carriers. vitamins and carotenoids) may have positive effects on bone health [36], they may hold therapeutic promise for osteopenia or osteoporosis in the m.3243A>G mutation carriers. In addition, we are the first to report a positive correlation between levels of glycated albumin and heteroplasmy levels of the mutant mtDNA.…”
Section: Discussionmentioning
confidence: 99%
“…Given that antioxidants (e.g. vitamins and carotenoids) may have positive effects on bone health [36], they may hold therapeutic promise for osteopenia or osteoporosis in the m.3243A>G mutation carriers. Moreover, measurement of BMD would appear to be valuable in the clinical management of m.3243A>G mutation carriers.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, no univocal data concerning the appropriate dosage for possible L supplementation had been found [ 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. More recently, a number of studies have suggested that L may indeed have favorable effects via anti-inflammatory activity [ 39 ], improving cognitive functions [ 40 ], and decreasing the risk of cancer [ 41 ], cardiovascular diseases [ 39 ] and other systemic conditions [ 42 , 43 , 44 ]. Overall, it seems that the amount of L intake, including by supplementation, may partly counter inflammatory processes and favor human health, but inconsistencies still remain.…”
Section: Introductionmentioning
confidence: 99%